MONITORING KONDISI TANAMAN HIDROPONIK DALAM BENTUK CITRA MELALUI IOT DENGAN MODUL ESP 32 CAM - Cahyono, Dwi Yoza; Hariono, Tholib (Lembaga Penelitian Pengabdian Masyarakat Universitas KH. A. Wahab Hasbullah, 2021)
Hydroponics is defined as the cultivation of plants without soil media. The origin of the word hydroponics is from the word hydro which means water and ponus which means power. Usually, the hydroponic system is carried out in a greenhouse due to certain factors such as an ecosystem that is easier to control, and limited land, and so on. plant growth should be monitored remotely, it is necessary to add a camera for optimization of growth monitoring, in addition to knowing the quality of plants or plants can be analyzed automatically with (RGB) good leaves and wilted leaves. This system consists of a pH sensor, Arduino UNO and of course the ESP 32 Camera